Towards solar power supply for copper production in Chile: Assessment of global warming potential using a life-cycle approach. (15th October 2017) - Moreno-Leiva, Simón; Díaz-Ferrán, Gustavo; Haas, Jannik; Telsnig, Thomas; Díaz-Alvarado, Felipe A.; Palma-Behnke, Rodrigo; Kracht, Willy; Román, Roberto; Chudinzow, Dimitrij; Eltrop, Ludger
Abstract: Solar energy technologies are a promising option to lower the greenhouse gas emissions of energy generation. Using solar technologies in energy-intensive industries located in arid climate zones is an attractive alternative for that purpose. In this work, the environmental benefit of integrating solar energy in the Chilean copper industry is explored in respect of global warming potential (GWP). A new life cycle assessment model for copper cathodes production in Chile and the integration of three solar technologies was developed. The GWP of the production of copper cathodes was calculated considering local representative conditions for climate, energy mix, and energy demand of the industry. It was computed at 6.0 tCO2eq /t Cu 2 for a pyrometallurgical process (P-Cu) and 4.9 tCO2eq /t Cu for a hydrometallurgical process (H-Cu). Further contributions of this paper are the consideration of the decline in ore grade (i.e. copper content in the mineral) and the interconnection of Chile's two main power grids as sensitivities to the baseline. The interconnection of the power grids causes a GWP-reduction of 22% for P-Cu and 37% for H-Cu. In parallel, the expected lower ore grade by 2020 would increase the GWP of copper production by 10% for P-Cu and 4% for H-Cu. If the electricity that is currently taken from the grid is exclusively fed by solar technologies, the reduction on the GWP of copper production would be up to 63% and 76% for P-Cu and H-Cu processes. These numbers do not represent the upper bound for the reduction on the GWP of copper production that can be achieved with solar technologies because the substitution of on-site fossil fuel combustion with solar energy is another interesting mitigation option, which was not considered in this study. In order to achieve even less carbon-intensive production processes, an improved understanding of the copper's industry energy flows and profiles is needed. This would allow to assess the integration of further solar energy technologies and conceive the future of solar copper mining . Highlights: The life cycle GWP of 2014 Chilean copper cathodes production is assessed. The upper bound for GWP savings by substituting the electricity from the grid with CSP and PV solar energy is calculated. The impact of the decreasing ore grade and Chile's grids interconnection on GWP is calculated.